A review for the coach & athlete: Part 1 - Publow, B. (1999)
Since the early 1970s the slide board has been traditionally used by speed skaters as a means of developing and refining ice technique in the off season, as well as providing a reasonable "in season" technical and endurance workout at times when ice conditions were not good. The popularity of the slide board has exploded with the recent growth of in-line speedskating, and the inclusion of lateral motion "slide" training in aerobics classes. Research has shown that most biomechanical (i.e., joint angles, contraction velocity, etc.) and physiologic parameters (i.e., VO2, blood lactate, etc.) exhibited during board skating are similar to those observed during on ice training. In general, slide board workouts are meant to be technical, rather than resistance workouts, although there certainly are physiologic benefits to be derived from a well-constructed slide board program. When executed properly, board skating can provide several specific benefits for the speed skater.